Media Representations of Heroism Among Argentinean Women Footballers - Escudero, Carolina; Tejedor Calvo, Santiago (Humanities Diliman: A Philippine Journal of Humanities, 2023)
This essay analyzes the relations of gender and culture portrayed in the media surrounding Argentine women’s football. Through an ethnography of Argentine media, we explore the interactions between society and the cultural meaning of the Argentinean women’s football team that, during the World Cup in France 2019, took different paths of action: first, their recognition of a patriarchal society; second, their coming together and promoting leadership; and third, their heroic actions promoting transformation. This championship led to various media narratives of the players as “heroines.” It is from this imposed identity that we examine their circumstances, understanding that as the representations of football players change—they are now seen as heroines, agents of influence (Hogg), or leaders (Pestana and Codina)—their achievements contribute to the enhancement of collective national pride. This study’s analysis is based on social media posts and news, qualitative interviews, and archival documentation from which it is possible to observe that new media narratives proclaim women’s football as a non-binary profession, empowering women’s success at the local and national levels.